2016
DOI: 10.1017/s0263574716000692
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and inverse dynamics analysis for a novel 3-PUU parallel mechanism

Abstract: SUMMARYThe modules of parallel tool heads with 2R1T degrees of freedom (DOFs), i.e., two rotational DOFs and one translational DOF, have become so important in the field of machine tools that corresponding research studies have attracted extensive attention from both academia and industry. A 3-PUU (P represents a prismatic joint, U represents a universal joint) parallel mechanism with 2R1T DOFs is proposed in this paper, and a detailed discussion about its architecture, geometrical constraints, and mobility ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The moving coordinate of the moving platform relative to the top frame can be expressed as (𝑥, 𝑦, 𝑧), namely the vector 𝑂 1 𝑂 = [𝑥, 𝑦, 𝑧] 𝑇 . The forward kinematic problem [18,19] can be solved as:…”
Section: Transmission Mechanism Analysismentioning
confidence: 99%
“…The moving coordinate of the moving platform relative to the top frame can be expressed as (𝑥, 𝑦, 𝑧), namely the vector 𝑂 1 𝑂 = [𝑥, 𝑦, 𝑧] 𝑇 . The forward kinematic problem [18,19] can be solved as:…”
Section: Transmission Mechanism Analysismentioning
confidence: 99%
“…A tripod mechanism is proposed based on the Prismatic-Universal-Universal Parallel Kinematic Machine (PUU-PKM) [24][25][26][27]. The proposed mechanism consists of a base frame; this frame contains a fixed bottom base and a fixed top base which are connected together through six vertical parallel guide ways, these parallel guide ways are distributed where each two are positioned at 120ₒ with respect to the base frame.…”
Section: Model Design Of the Portable Cnc Machine And The Working Principalmentioning
confidence: 99%
“…However, 6-DOF parallel mechanisms have a small workspace and poor orientation capability. 16 Walker et al found that the simulator had significantly smaller mediolateral and dorsal-ventral displacements than a real horse. 9 To enlarge the workspace and improve the orientation capability, the size of the parallel mechanism must be large, in which case the device becomes too big, and interference may occur between the device and the rider's body.…”
Section: Horseback-riding Simulator Designmentioning
confidence: 99%